Transformational Leadership and Sustainable Development in Nigeria: Bridging the Gap between Policy and Implementation - Ogbe, Ekoja Bernard (Kashere Journal of Politics and International Relations, 2025)
The concept of transformational leadership is essential for driving sustainable development in Nigeria, particularly in addressing the persistent gap between policy formulation and implementation. Despite the establishment of numerous national and international development policies, including the Sustainable Development Goals (SDGs), Nigeria continues to face challenges such as poor governance, corruption, weak institutional capacity, and lack of accountability, which hinder effective implementation. This paper explores the role of transformational leadership in bridging this gap by fostering visionary thinking, ethical governance, innovation, and strategic execution. Transformational leaders inspire and mobilize stakeholders, creating a culture of accountability and encouraging innovative solutions to developmental challenges. By emphasizing intellectual stimulation and individualized consideration, transformational leaders empower communities and institutions to adopt sustainable practices across key sectors such as energy, agriculture, infrastructure, and education. Moreover, transformational leadership enhances policy advocacy and institutional reforms, ensuring that development efforts are aligned with long-term environmental, social, and economic priorities. The paper argues that sustainable development in Nigeria requires leaders who can translate policy objectives into measurable outcomes by driving collaboration between government agencies, private sector actors, and civil society. Transformational leadership not only strengthens institutional frameworks but also cultivates a culture of resilience and adaptability, positioning Nigeria to achieve inclusive and sustainable growth. This study highlights the transformative potential of visionary leadership in overcoming governance barriers and ensuring that sustainable development initiatives yield tangible and lasting benefits for future generations.